Manifestasi Klinis Infeksi Parasi Usus pada Anak: Literature Review - Nirwan, Qurratul Aina; Mutiara, Hanna; Suharmanto, Suharmanto; Wardani, Dyah Wulan Sumekar Rengganis (Medula, 2024)
Intestinal parasitic infection is a disease that still neglated, more likely found in developing countries. This infection is caused by a group of intestinal protozoa and worms, generally intestinal nematodes. In children, the STH group is the most common cause of infection. Infection often occurs via the fecal-oral route. Children more often consume infective stages to other age groups due to their poor hygiene behavior.  Intestinal parasitic infections in children can cause high mortality and mobility. This infection causes a decline in health conditions, nutritional absorption, intelligence and productivity. This can simultaneously cause disruption of growth and development in children. These manifestations are related to the virulence of the parasite strain, the number of infective stages consumed, the age of the patient, and the state of the immune system at the time of infection. Apart from that, the manifestations that arise are widespread, asymptomatic to chronic. The manifestions are related to the digestive tract as the target organ of infections. However, manifestations can also be found outside the digestive tract. This is because organisms move to other organs through blood vessels. Manifestations that arise in the digestive tract are usually nausea, vomiting, abdominal pain, constipation, and diarrhea which is sometimes accompanied by blood. Not only that, weakness, fatigue, lethargy, and eating disorders are the manifestation of these infections. This is what causes growth and development disorders in children. Meanwhile, the extraintestinal mainifestations are liver abscess due to amoeba infection, Loeffler syndrome due to Ascaris lumbricoides infection and other manifestations. Usually, the intestinal nematoda infections caused have their own characteristics.